Antonyms in the Animation of “KKN di Desa Penari” From Rizky Riplay’s Youtube Account - Riajeng Woro Megaswari; Sumarlam Sumarlam (Faculty of Humanities, Universitas Jenderal Soedirman, 2020)
This study aims to describe the cohesiveness of the discourse in terms of the lexical cohesion aspects of the use of antonymy in an animated story about